Fungal Decontamination of Fleshy Fruit Water Washes by Double Atmospheric Pressure Cold Plasma. Issue 2 (10th December 2015) - Ouf, Salama A.; Mohamed, Abdel‐Aleam H.; El‐Sayed, Wael S.
Abstract : The washwater from strawberries had the highest level of contamination by fungal species compared to washwater from cherries or red grapes. The fungal counts in the washwater from moldy fruits were much higher than those recovered from healthy fruits. Aspergillus niger and Penicillium italicum were the most dominant fungi isolated from the fruit washwater. Treatment of the washwater with double atmospheric pressure cold plasma (DAPCP) for 7.5 min induced a significant reduction in the colony forming units of fungal species that reached 74.7–100% in the washwater of cherries. The variation in plasma efficacy for the different samples was dependent on the level of antioxidants in the washwater, which attenuated the oxidizing radicals and reduced the life span of the reactive species generated by the plasma, particularly oxygen radicals. Upon DAPCP treatment, the spores of A. niger exhibited electroporation in their walls. The treatment of the washwater with DAPCP for 9 min induced a steady reduction in the amount of mycotoxins in the washwater of moldy fruits, reaching reductions of 87.93, 66.42, and 72.00% for aflatoxins, fumonisins, and ochratoxins, respectively, in the washwater from cherries. Abstract : Treatment of water from washing of cherries, strawberries, and red grapes with double atmospheric pressure cold plasma induced a significant reduction in the colony forming units of contaminated fungal species depending on the investigated fruit. The variation in plasma efficacy for the different samples was related to the level of antioxidants in the water, which attenuated the oxidizing radicals of the plasma, particularly oxygen radicals.